Constructions and details for fixing magnetically operated sealed switches in the closed electrical pathways; Mechanical Engineering, Automation and Control Systems (MEACS) - Kletsel M. Ya. Mark Yakovlevich; Berguzinov A. N.; Alishev Z. R.; Goryunov V. N. (2014, 2014)
Title screen